Influence of coupled support on livestock farming sector development in Romania - Mariana Grodea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Coupled support is one of the main payment schemes in the category "direct payments", introduced at EU level in the year 2015, funded from the European Agricultural Guarantee Fund (EAGF). In the EU-28, the highest share of coupled support payments in the year 2019 went to the livestock farming sector (73.2%), of which 39.7% in the beef cattle sector, 20.9% in the dairy cow sector and 12.6% in the sheep and goat sector. In the period 2015-2019, the livestock farming sector in Romania benefited from coupled support worth 668.9 million euros, out of which 60.7% in the dairy sector, 30.5% in the sheep and goat sector, 7.8% for beef cattle and 1% in the dairy buffalo sector. The results obtained following the analysis of statistical data for the period when this payment scheme was implemented (2015-2020) reveal that in the case of cattle sector, there was a non-significant impact on this sector development, in the sense that the decline continued both in terms of the total number of animals (-217 thousand heads), of meat production (-27.1 thousand tons live weight) and cow milk production (-2.8 million hl). The sheep and goat sector had a positive evolution in the same period, both as regards the number of animals (+629 thousand heads), meat production (+11 thousand tons live weight), yet with the decrease of slaughters in specialized units (-4.7 thousand tons live weight).
Keywords: Q10; Q13; Q19; 330; coupled support; beef cattle; dairy cows; buffalo cows; sheep; goats